2015
DOI: 10.1155/2015/236749
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning Laboratory for Teaching Embedded Systems

Abstract: This paper presents a project-based learning laboratory for the teaching of embedded systems. The main objectives are to encourage students studying the embedded systems course in developing hardware solutions for real engineering problems and to include aspects of other courses studied within the academic programmes. One of the aims of project-based learning (PRBL) is to integrate different courses in the achievement of a common objective, within a multidisciplinary course of the academic programme. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…All details associated with the project (implemented in 2012.2) are presented in Fernandes. 30 Figures 5 and 6 illustrate the projects developed by the students in semesters 2012.2 and 2013.2, respectively. In 2012.2, the project involved control of the…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…All details associated with the project (implemented in 2012.2) are presented in Fernandes. 30 Figures 5 and 6 illustrate the projects developed by the students in semesters 2012.2 and 2013.2, respectively. In 2012.2, the project involved control of the…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…To evaluate the effectiveness of this combined project on student learning towards the defined learning objectives, we developed a survey based on similar PjBL approaches [6][7][8][9][10][11][12]. The survey is divided into four sections as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Project-based learning (PjBL) is an interactive studentcentered learning strategy that has proven effective in providing realistic context to the students, helping them to integrate knowledge from lectures, and developing teamwork and communication skills [7][8][9][10][11]. In addition, a multicourse project offers the advantage of integrating different concepts under the same context [12].…”
Section: Introductionmentioning
confidence: 99%
“…Developing tools that support model-based construction and delivery of sophisticated education that assists students and practioners master the complexity of developing embedded software and systems has been underway for several years, and it can be observed significant positive changes in the Vanderbilt University, America students give feedback, on the senior design project has been extremely positive [2]. The result of the student of University of Rio Grande do Norte, Brazil regarding the entire methodology employed in the class, it could be concluded that the Project-Based Learning Laboratory for Teaching Embedded Systems methodology was well received, since score 4 or 5 was given in more than 90%of the responses [3].…”
Section: Introductionmentioning
confidence: 91%